2017
DOI: 10.5607/en.2017.26.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Orai1 and Orai3 in Combination with Stim1 Mediate the Majority of Store-operated Calcium Entry in Astrocytes

Abstract: Astrocytes are non-excitable cells in the brain and their activity largely depends on the intracellular calcium (Ca2+) level. Therefore, maintaining the intracellular Ca2+ homeostasis is critical for proper functioning of astrocytes. One of the key regulatory mechanisms of Ca2+ homeostasis in astrocytes is the store-operated Ca2+ entry (SOCE). This process is mediated by a combination of the Ca2+-store-depletion-sensor, Stim, and the store-operated Ca2+-channels, Orai and TrpC families. Despite the existence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 43 publications
(56 reference statements)
3
38
0
Order By: Relevance
“…Nevertheless, a recent investigation clearly showed that heteromeric Orai1/Orai3 channels mediate Stim1- and Stim2-dependent SOCE induced by 5α-dihydrotestosterone (DHT) in LNCaP cells [ 33 ]. In addition, Stim1, Stim2, Orai1 and Orai3 were found to mediate SOCE in mouse dorsal root ganglion neurons [ 74 ] and mouse astrocytes [ 75 ]. Finally, Orai1 and Orai3 were shown to mediate Ca 2+ entry in response to store depletion in mouse pulmonary artery smooth muscle cells [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a recent investigation clearly showed that heteromeric Orai1/Orai3 channels mediate Stim1- and Stim2-dependent SOCE induced by 5α-dihydrotestosterone (DHT) in LNCaP cells [ 33 ]. In addition, Stim1, Stim2, Orai1 and Orai3 were found to mediate SOCE in mouse dorsal root ganglion neurons [ 74 ] and mouse astrocytes [ 75 ]. Finally, Orai1 and Orai3 were shown to mediate Ca 2+ entry in response to store depletion in mouse pulmonary artery smooth muscle cells [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…1), which is present in astrocytes (48,53). AC8 can be activated by SOCE in the absence of GPCR activation, perhaps in part due to a physical association with Orai1 channels (55)(56)(57), although the relative roles of TRPC vs. Orai channels for mediating SOCE remains controversial (58,59). Clearly, SOCE represents a non-receptor-mediated way of initiating Ca 2+ /cAMPdependent glycogen breakdown; however, in situ SOCE would only occur following an initial cytosolic Ca 2+ signal depleting intracellular Ca 2+ stores such as a GPCR-Gαq-IP3-mediated store depletion.…”
Section: Putative Role Of Non-receptor-coupledmentioning
confidence: 99%
“…If the [Ca 2+ ] i activities are controlled by multiple parallel or independent processes, the spatiotemporal parameters of the [Ca 2+ ] i fluctuations should follow a standard gaussian normal distribution according to the central limit theorem (21). However, the spatiotemporal characteristics of [Ca 2+ ] i peaks (e.g., number for multiple peaks from a single cell, time it takes to reach a peak from the baseline) of the same cell population were found to follow a lognormal distribution rather than a normal distribution (22,23). Little knowledge is available to interpret this statistical distribution profile of the [Ca 2+ ] i peak parameters.…”
Section: Spontaneous [Camentioning
confidence: 99%